Does remittance inflow influence human development in south Asian countries? An empirical insight. Issue 4 (28th July 2020) - Sahoo, Malayaranjan; Sucharita, Sanhita; Sethi, Narayan
Abstract: This article investigate the relationship between human development, remittance inflows, and other macroeconomic variables like life expectancy, human capital, FDI, CPI, economic growth, and financial development in South Asia during 1990–2018. The Fisher residual co‐integration test confirms that there is a co‐integration among the variables. The VECM approach also indicates that there is a long run relationship among the variables. We apply FMOLS and DOLS to show the long run elasticity of explanatory variables in this article. Remittance indicates positive and significant effect on human development. We find that there is a positive effect between government expenditure and human development. Similarly, life expectancy rate and human capital has a positive effect on human development. There is a unidirectional causality between remittance and human development in South Asian region. We can suggest that public policies can be conceived to promote health, education, and income, thereby encouraging and enhancing human development.